Remittance Trends 2007 - Ratha, Dilip; Mohapatra, Sanket; Vijayalakshmi, K. M.; Xu, Zhimei (World Bank, Washington, DC, 2012)
This note describes broad regional and country specific trends in remittance flows worldwide, and highlights some structural changes that will affect remittance flows in the future. The main messages are: remittance flows to Latin America and the Caribbean slowed on the back of a weakening U.S. economy and tighter enforcement of immigration laws. Nevertheless, the growth of remittances to developing countries remains robust because of strong growth in Europe and Asia. The remittance industry is experiencing some positive structural changes with the advent of cell phone and internet-based remittance instruments. These changes may have profound effects on remittance flows to previously underserved areas. The diffusion of these structural changes, however, is slowed by a lack of clarity on key regulations (including those relating to money laundering and other financial crimes). Remittance costs have fallen, but not far enough, especially in the South-South corridors.